Genomic and transcriptomic insights into methanogenesis potential of novel methanogens from mangrove sediments - Zhang, Cui-Jing (Microbiome, 2020)
BACKGROUND: Methanogens are crucial to global methane budget and carbon cycling. Methanogens from the phylum Euryarchaeota are currently classified into one class and seven orders, including two novel methanogen taxa, Methanofastidiosa and Methanomassiliicoccales. The relative importance of the novel methanogens to methane production in the natural environment is poorly understood. RESULTS: Here, we used a combined metagenomic and metatranscriptomic approach to investigate the metabolic activity of methanogens in mangrove sediments in Futian Nature Reserve, Shenzhen. We obtained 13 metagenome-assembled genomes (MAGs) representing one class (Methanofastidiosa) and five orders (Methanomassiliicoccales, Methanomicrobiales, Methanobacteriales, Methanocellales, and Methanosarcinales) of methanogens, including the two novel methanogens. Comprehensive annotation indicated the presence of an H(2)–dependent methylotrophic methanogenesis pathway in Methanofastidiosa and Methanomassiliicoccales. Based on the functional gene analysis, hydrogenotrophic and methylotrophic methanogenesis are the dominant pathways in mangrove sediments. MAG mapping revealed that hydrogenotrophic Methanomicrobiales were the most abundant methanogens and that methylotrophic Methanomassiliicoccales were the most active methanogens in the analyzed sediment profile, suggesting their important roles in methane production. CONCLUSIONS: Partial or near-complete genomes of two novel methanogen taxa, Methanofastidiosa and Methanomassiliicoccales, in natural environments were recovered and analyzed here for the first time. The presented findings highlight the ecological importance of the two novel methanogens and complement knowledge of how methane is produced in mangrove ecosystem. This study implies that two novel methanogens play a vital role in carbon cycle.